Gut-brain axis mediated by intestinal content microbiota was associated with Zhishi Daozhi decoction on constipation - Leyao Fang; Leyao Fang; Leyao Fang; Xin Yi; Xin Yi; Junxi Shen; Junxi Shen; Na Deng; Na Deng; Xinxin Peng; Xinxin Peng (Frontiers in Cellular and Infection Microbiology)
BackgroundConstipation is a common digestive system disorder, which is closely related to the intestinal flora. Zhishi Daozhi decoction (ZDD) is a traditional Chinese medicine prescription used to treat constipation caused by indigestion. This study is to evaluate the efficacy of ZDD in treating constipation and to elucidate the underlying mechanism.MethodsIn this study, Kunming mice were administered a high-protein diet (HFHPD) and loperamide hydrochloride injections to induce constipation. The mice then received varying doses (2.4, 4.7, and 9.4 mg/kg) of ZDD for seven days. Following the sampling process, we measured fecal microbial activity. The levels of 5-hydroxytryptamine (5-HT), vasoactive intestinal peptide (VIP), and aquaporin-3 (AQP3) were quantified using enzyme-linked immunosorbent assay. Changes in the gut microbiota were evaluated through 16S rRNA gene sequencing. Additionally, we investigated the correlation between specific microbiota features and the levels of 5-HT, VIP, and AQP3.ResultsThe fecal surface of the mice in the model group (CMM) was rough and dry. The stool of mice in the low-dose ZDD group (CLD), medium-dose ZDD group (CMD), and high-dose ZDD group (CHD) exhibited a smoother texture, closely resembling that of the normal group (CNM). 5-HT levels in the CMM group were significantly lower than in the CNM, CLD, and CHD. VIP levels in the CMD were lower than in the other four groups, and AQP3 levels in CMM showed a decreasing trend. The fecal microbial activity of the CMM group was significantly higher than that of the other groups. Diversity analysis indicated that CMD and CHD treatments were more effective in restoring the intestinal microbiota structure. Potential pathogenic bacteria, including Clostridium, Aerococcus, Jeotgalicoccus, and Staphylococcus were enriched in CMM. In contrast, beneficial bacteria such as Faecalibacterium, Bacillaceae, and Bacillus were more prevalent in the CLD, CMD, and CHD. Correlation analysis revealed that Streptococcus and Enterococcus were positively correlated with VIP, while Succinivibrio showed a negative correlation with 5-HT.ConclusionsConstipation induced by HFHPD and loperamide hydrochloride disrupts the structure of the intestinal microbiota. ZDD appears to alleviate constipation, potentially through mechanisms linked to the brain-gut axis and its interaction with the intestinal microbiota. Among the treatment groups, the medium dose of ZDD demonstrated the most effective results.